Motorcycle Safety System Using RFID and GPS Based on ESP32 Internet of Things - Maulana, Indra; Misbah, Misbah (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
Motorbikes are an alternative transportation for the majority of lower middle class Indonesians, because motorbikes have affordable prices, low maintenance costs, and are fuel efficient. The increasingly rapid use of motorbikes also increases the speed of criminal acts, namely motorbike theft, because apart from user error, the built-in security system of motorbikes can still be hacked, which can trigger theft. To overcome this, a security system was added with tools that can monitor and control remotely. This system utilizes RFID to recognize registered IDs. To turn it on, you can only use the ID that has been registered. Then the ESP 32 which is connected to Mifi is the brain that processes the motorbike and will send notifications and locations using the GPS module to the user via telegram. If the ID used is not registered and you tap 3 times/the motorbike is indicated to be stolen, a danger notification will be sent to the user via telegram. Users can also send commands back to the motorbike remotely via telegram. The results of this research show that the efficient RFID distance is 1-3 cm because there is no error (0%), and GPS accuracy has an average error of 3.3 meters, as well as suitability for use of the Telegram application.